Ecotheological Curriculum Innovation: Integrating Creation Care Ethics and Experiential Learning Strategies in Christian Higher Education Institutions - Rezeki Putra Gulo; Rheinhard David Sutrisno; Jonius Halawa (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Study explores the integration of eco theology into Christian higher education curricula, focusing on the role of faith based environmental education in fostering environmental stewardship. Introduction: As the global ecological crisis intensifies, there is a growing need to incorporate ecological ethics into religious education, preparing future leaders to address environmental challenges. By integrating eco theology with sustainability practices, students are encouraged to view environmental stewardship as a spiritual responsibility grounded in biblical teachings. Literature Review: Previous studies emphasize the success of faith based educational approaches in raising ecological awareness and fostering sustainable practices, particularly in Islamic and Christian communities. Eco theology combines theological principles with environmental ethics, offering a holistic perspective on sustainability. Materials and Method: This study employs a mixed methods approach, combining qualitative and quantitative data from interviews, surveys, and focus groups with students and faculty members at Christian institutions that integrate eco theology into their curriculum. The research examines changes in students' attitudes toward sustainability before and after participation in eco theology courses, focusing on practical applications of creation care. Results and Discussion: The findings indicate that the integration of eco theology significantly enhances students' ecological awareness and commitment to sustainability practices. Students report an increased understanding of the ethical and moral responsibility to care for creation, as well as greater engagement in community based conservation efforts. The results highlight the potential of eco theology as a transformative model in Christian higher education, equipping students with both ethical and practical tools to address the global ecological crisis.